2000
DOI: 10.1093/toxsci/57.1.131
|View full text |Cite
|
Sign up to set email alerts
|

PCBs, Thyroid Hormones, and Ototoxicity in Rats: Cross-Fostering Experiments Demonstrate the Impact of Postnatal Lactation Exposure

Abstract: Previous research has demonstrated the sensitivity of the developing rat to the hypothyroxinemic and ototoxic effects of perinatal exposure to Aroclor 1254 (A1254). We tested the hypothesis that postnatal exposure via lactation is the major cause of the ototoxicity by cross fostering animals at birth. Primiparous rats (22-24/dose) received 0 or 6 mg/kg A1254 (po in corn oil) from gestation day (GD) 6 to postnatal day (PND) 21. On the day of birth, half of the treated litters and half of the control litters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
51
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 69 publications
11
51
0
Order By: Relevance
“…Our results suggest that A1221 may alter the amount of time that females choose to spend with males after a mating event. Consistent with this, other reports on PCBs have shown effects on other sensory and motor parameters in many systems, including audition (Crofton et al, 2000), sensory and motor nerve conduction velocities (Chen et al, 1985) and vision (Kremer et al, 1999).…”
Section: A1221 Effects On Paced Mating Behaviorssupporting
confidence: 87%
See 1 more Smart Citation
“…Our results suggest that A1221 may alter the amount of time that females choose to spend with males after a mating event. Consistent with this, other reports on PCBs have shown effects on other sensory and motor parameters in many systems, including audition (Crofton et al, 2000), sensory and motor nerve conduction velocities (Chen et al, 1985) and vision (Kremer et al, 1999).…”
Section: A1221 Effects On Paced Mating Behaviorssupporting
confidence: 87%
“…Our results suggest that A1221 may alter the amount of time that females choose to spend with males after a mating event. Consistent with this, other reports on PCBs have shown effects on other sensory and motor parameters in many systems, including audition (Crofton et al, 2000), sensory and motor nerve conduction velocities (Chen et al, 1985) and vision (Kremer et al, 1999).Not all aspects of the suite of mating behaviors were significantly affected by early PCB treatment. We did not detect significant differences in lordosis quotient (LQ) among treatment groups, although there was a non-significant trend for the highest LQ in the 1 mg/kg group.…”
supporting
confidence: 84%
“…However, the slight prolongation of latencies in metaboliteexposed groups may indicate effects on the neural part of the auditory system. Alternatively, this may be explained by the observations of Crofton et al (2000b), who showed in crossfostering studies that lactational exposure to Aroclor (postnatally) is the major cause of ototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, experimental animals appear to be especially sensitive to PCB exposure during the postnatal period as manifested by levels of thyroxine, which are similarly reduced after in utero followed by postnatal dosing (perinatal; Crofton et al, 2000;Goldey et al, 1995;Shah et al, 2011). In support of this, others have shown that perinatal dosing can alter levels of male reproductive steroids in adulthood (Hany et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…levels (Bowers et al, 2004;Crofton et al, 2000;Hany et al, 1999) and postnatal or adult exposure reduces reproductive function in male and female rats (Jonsson et al, 1975;Sager, 1983). In human studies developmental exposure to Aroclor 1254 has been associated with attention and learning deficits in children (Jacobson and Jacobson, 2003) and with abnormal reproductive function and reduced testosterone (Bell, 2014).…”
Section: Introductionmentioning
confidence: 99%